استخدام نظام المعلومات التسويقية في اتخاذ قرار سياسة المنتج (دراسة حالة: مؤسسة اتصالات الجزائر موبيليس (ATM)) - ميلود, تومي; فراح, خالدي (Recherches économiques et managériales; Vol. 13 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (JUIN))
أصبح نظام المعلومات التسويقية في السنوات الأخيرة من أهم الأدوات التي يعتمد عليها المسؤولين عن التسويق في المؤسسات، حيث نجد عددا كبيرا منها يحاول التوجه نحو تبني نظام معلومات تسويقية فعال يساهم في ربط كافة سياسات المؤسسة مع بعضها لتحليلها بشكل متكامل، وبتالي استخراج معلومات تسويقية تفصيلية تساعد في اتخاذ القرارات التسويقية المختلفة، خاصة القرارات المتعلقة بالمنتج، كما هو حال مؤسسة اتصالات الجزائر (موبيليس)، فدراستنا تهدف إلى تقييم نظامها للمعلومات التسويقية، ومدى استجابة موظفيها له، وخلصت إلى مجموعة من التوصيات من شأنها تعزيز الاعتماد على المعلومات التسويقية في النشاط التسويقي للمؤسسة. الكلمات المفتاح: نظام المعلومات التسويقية، اتخاذ قرارات التسويقية، سياسة المنتج. The Abstract :      T he system  of marketing information became in the last years the most important tools that relied upon  those responsible  marketing  institutions, where we found a large number of them trying to go about adopting a marketing information effectively by which it contributes to connect all corporate policies with each other to be analyzed in an integrated manner, and hence to have an extract marketing information detailed to help in the various marketing decision-making , and other private decisions regarding to the product policies, as in the case of Algerian Telecom Foundation (Mobilis), where our study aimed at assessing its marketing information , and the response of its employees, also to found a set of recommendations that will strengthen the reliance on the marketing information in the marketing activity of the institution . Key words: The system of marketing information, marketing decision-making, product policy .